Lewatit-immobilized lipase from Bacillus pumilus as a new catalyst for biodiesel production from tallow: response surface optimization, fuel properties and exhaust emissions - Shabbir, Aroosh; Mukhtar, Hamid; Mumtaz, Muhammad Waseem; Rashid, Umer; Abbas, Ghulam; Moser, Bryan R.; Alsalme, Ali; Touqeer, Tooba; Ngamcharussrivichai, Chawalit (Elsevier, 2022)
Biodiesel is currently regarded as a sustainable and renewable alternative to depleting fossil fuels such as petro-diesel. Biodiesel production on a large scale could have a positive impact on the energy sector and the environment by lowering greenhouse gas emissions. Disadvantages of biodiesel include utilization of high-cost edible oils for production of biofuels, generation of wastewater and inability to recycle catalysts after alkaline-catalyzed methanolysis. The objectives of the current study were to utilize low-cost, inedible tallow to produce biodiesel from Lewatit-immobilized lipase produced from Bacillus pumilus and to measure the fuel properties and exhaust emissions of the resulting fatty acid methyl esters. Response surface methodology was used to optimize reaction conditions and alkaline (potassium hydroxide; KOH) catalysis was performed for comparison. A conversion of 96% was achieved by two step chemical-mediated transesterification, whereas conversion was 67% for the single step lipase-mediated method. Acid pre-treatment was needed in the case of KOH-catalyzed transesterification to reduce the acid value of tallow from 17.6 to 1.3 mg KOH/g, whereas the Lewatit-immobilized lipase was able to efficiently catalyse both transesterification of glycerides and esterification of free fatty acids. To the best of our knowledge, the lipase from B. pumilus has not yet been studied for biodiesel production from tallow. Fuel properties of the resulting optimized biodiesel were within the limits prescribed in ASTM D6751 and EN 14214. In addition, exhaust emissions studies revealed reduced CO and PM relative to petro-diesel. In both cases, reductions were greater as the percentage of biodiesel increased in blends with petro-diesel. However, NOx emissions were elevated versus petrodiesel in blends that contained 50% or more of biodiesel. This research reveals new ways for utilization of waste animal fats for biodiesel production as well as a new efficient lipase source that yields more products and provides environmental and economic security.